Coarse woody debris provides cobenefits between carbon stock and diversity of polypore fungi in Malaysian forest stands - Yamashita, Satoshi; Salleh, Habibah; Wasli, Mohd Effendi; Alias, Mohamad Azani; Itioka, Takao; Kenzo, Tanaka; Ichie, Tomoaki (Japan Society of Tropical Ecology, 2022)
There is a high expectation for forest ecosystems to provide several ecosystem services simultaneously. In this study, positive relationships between the amount of carbon stock in coarse woody debris (CWD) and the diversity of polypore fungi were examined in six primary stands and 19 secondary stands with different stand ages (12-81 years) of tropical rain forests in Malaysia. We recorded the size and number of each of the CWD pieces in which at least one fruiting body of 21 target polypore species appeared in each plot. The average amount of carbon stock in the CWD pieces was estimated to be 48.8 Mg ha－1 in primary forests and 12.3 Mg ha－1 in secondary forests. The diversity of polypore species increased with the amount of carbon stock in CWD when data from primary and secondary forest were combined. Among secondary forests, the carbon stock of CWD increased with stand age, but diversity of polypore species varied greatly among stands of similar ages and the carbon stock of CWD, and hence did not significantly increase with stand age or the carbon stock of CWD. According to our findings, primary forests are critically important for the conservation of biodiversity and carbon stock, and old secondary forests with higher carbon stock in CWD have a potential to sustain a high level of diversity of polypore fungi.